2017
DOI: 10.3390/ma10080965
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pullulan Coating on Postharvest Quality and Shelf-Life of Highbush Blueberry (Vaccinium corymbosum L.)

Abstract: Fruits form an important part of a healthy human diet as they contain many ingredients with proven pro-health effects such as vitamins, phenolic compounds, organic acids, fiber, and minerals. The purpose of this work was to evaluate the effect of pullulan coating on the quality and shelf life of highbush blueberry during storage. General appearance, weight loss, dry matter, soluble solid content, reducing sugars, content of L-ascorbic acid, phenolic compounds (total phenolics, phenolics acids and anthocyanins)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 42 publications
1
31
0
Order By: Relevance
“…Pullulan‐based coatings offer, in comparison to other polymer substances, great glue properties, high mechanical strength, and nonresponsive with food ingredients (Kraśniewska et al, ). In general, pullulan coatings have demonstrated no shading, no taste, no scent, and restricted permeability to oxygen and carbon dioxide gases (Wu & Chen, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pullulan‐based coatings offer, in comparison to other polymer substances, great glue properties, high mechanical strength, and nonresponsive with food ingredients (Kraśniewska et al, ). In general, pullulan coatings have demonstrated no shading, no taste, no scent, and restricted permeability to oxygen and carbon dioxide gases (Wu & Chen, ).…”
Section: Introductionmentioning
confidence: 99%
“…In general, pullulan coatings have demonstrated no shading, no taste, no scent, and restricted permeability to oxygen and carbon dioxide gases (Wu & Chen, ). Pullulan was also recognized as difficult to absorb carbon source which was not utilized by food spoilage microbes (Kraśniewska et al, ; Viškelis, Rubinskienė, Sasnauskas, Bobinas, & Kviklienė, ). These excellent qualities attribute pullulan coatings as edible “active” coatings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the incorporation of AKEO improved the resistance to moisture loss and water vapor barrier properties of the chitosan film. Pullulan is a nonionic polysaccharide with good adhesiveness and film formability [15]. Pullulan membranes are nearly impenetrable to gases such as O 2 , N 2 , CO 2 and aromas at low relative humidity (RH) [16].…”
Section: Introductionmentioning
confidence: 99%
“…4 Many studies have shown the use of pullulan coatings to increase the shelf-life of fruits. 5 Pullulan coatings had good adhesive properties, high mechanical strength and did not react with food ingredients. In addition, pullulan coatings were colorless, tasteless and odorless, and had limited permeability to gases, such as oxygen and carbon dioxide.…”
Section: Introductionmentioning
confidence: 99%